A.M. Klein’s The Rocking Chair: Toward the Redefinition of the Poet’s Function - Brenner, Rachel Feldhay (Studies in Canadian Literature, 1990)
Brenner argues against the stasis of ideological signification when discussing poetry, asserting that despite Klein’s overt humanist ideology in this volume of poetry, the book is a production rather than a product; the complex voice of art often refutes ideological simplifications. For one thing, the poems become progressively more satirical towards the end of the book, the speaker increasingly alienated. Klein parodies Milton and Joyce: their shared belief in the primacy of art is belied by Klein’s assertion of "the deposition of the poet" in the twentieth century by economic and scientific powers. Some of the poems examine and compare the Jewish and the French experience in Canada.